Diagnostic Accuracy of MRI and CT Scan in Non-Invasive Evaluation of Liver Cirrhosis: MRI and CT Scan in Evaluation of Liver Cirrhosis - Hassan, Syed Hira; Khan, Fida Muhammad; Afridi, Salman; Younas, Muhammad; Khan, Asif; Ibrahim, Munazza; Rafiullah, .; Sajjad, Muhammad (Pakistan Journal of Health Sciences, 2024)
Liver cirrhosis is a chronic, non-reversible disease which results from fibrosis of the healthy liver tissue and compromise of its functioning. Adequate diagnostic procedures that do not involve invasive procedures are necessary for early diagnosis of cirrhosis to minimize the risk of complications. Even though liver biopsy is considered the gold standard, this procedure is invasive and thus, non-invasive imaging studies, including Megnatic Resonance Imaging and Computed Tomography scan must be further emphasized. Objective: To determine the diagnostic accuracy of combination imaging techniques MRI and CT scan in the non-invasive assessment of liver cirrhosis taking histopathology as gold standard. Methods: This cross-sectional study was conducted at the department of Gastroenterology, Hayatabad Medical Complex, Peshawar, during the period 1st July 2023 till 30th June 2024. Male and female patients aging 18 to 80 years with suspected liver cirrhosis on ultrasound were enrolled. MRI and CT scan of the liver were carried out and the findings were compared with histopathology to draw the diagnostic accuracy. Results: The study comprised of 75 (58.6%) male and 53 (41.4%) female. The mean age was 55.4 ± 7.2 years. Liver morphology in patients with cirrhosis had sensitivity of 96.8% and specificity of 100%, with the PPV of 100% and NPV of 33.3%. For vascular features the sensitivity was 88.9% and a specificity of 30.0% respectively, with the PPV of 93.7% and an NPV of 18.7%. As an imaging finding, ascites had a sensitivity of 46.0% and a specificity of 59.6%, with a PPV of 62.5% and an NPV of 43.0%. Conclusion: Combining non-invasive imaging modalities like MRI and CT scan enhances the diagnostic accuracy in detecting liver cirrhosis and the degree of fibrosis.